A SYSTEMATIC REVIEW ON IDENTIFICATION OF EXCITATION SYSTEMS FOR SYNCHRONOUS GENERATORS (REVISIÓN SISTEMÁTICA EN IDENTIFICACIÓN DE SISTEMAS DE EXCITACIÓN PARA GENERADORES SINCRÓNICOS) (2013)
This paper presents the state of the art on system identification applied to excitation systems. First, general overviews about system identification and excitation systems for synchronous generators are presented, highlighting the unique characteristics imposed by the excitation systems in an identification process. Then, a bibliographic classification method based on the excitation system characteristics was designed, which provides a results matrix condensing the topics addressed by more than 40 reviewed publications. From the results analysis the state of the art in excitation system identification was established, and open research areas in the topic were recognized.Resumen: Luego se presenta el diseño de un método de clasificación basado en las características de los sistemas de excitación. El resultado del método es una matriz que condensa los asuntos discutidos en más de 40 publicaciones. El estado se establece desde el análisis de los resultados y adicionalmente se reconocen áreas abiertas de investigación en la identificación de sistemas de excitación.